FACTORS SUCCESS OFF PUPILS OF SECONDARY SCHOOLS IN KOSOVO WITH SPECIAL REFERENCE TO OF PHYSICAL ACTIVITY AND SPORTS ACTIVITIES - Abedin Ibrahimi; Vildane Jashari; Ismajl Jashari (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
In this paper are presented the emperical results of verification of factors that affect students success of high schools in Kosova. It's presented metodology of research and are given all results preliminary of anlalysis to all variables,in which the research is based. In this group of factors entered also physical activity and sport,and neither all circumstancers socio-economic wher live the all tested people.